Silent Lacunary Brain Infarctions Associated with Left Ventricular Noncompaction and Idiopathic Epilepsy A Case Report (Global Journal of Medical Research, 2018)
Left ventricular noncompaction is a rare cause of cardiomyopathy, sometimes with a family character that may complicate evolving with heart failure, heart rhythm disorders and systemic embolic events -including stroke. We report a case of a young patient in neurological dispensary for epilepsy where the neuroimaging evaluation of an acutely installed cephalalgia syndrome revealed multiple silent lacunar brain injuries. Paraclinical examinations of their etiology have led to the diagnosis of a left ventricular noncompaction, in this context the lacunar infarcts beeing considered as cerebral embolic events with a cardiac starting point.
Keywords: left ventricular noncompaction; silent lacunar infarction